Performance Improvement of a Solar-Powered Recompression Supercritical Carbon Dioxide Cycle by Introducing an Ammonia-Water Cooling-Power System - Zhang, Yicen; Du, Yang; Lu, Xiaochen; Zhao, Pan; Dai, Yiping (Frontiers in Energy Research, 2022)
The wide utilization of solar energy is beneficial for the emission reduction of carbon dioxide. This paper proposes a novel power cycle system driven by solar energy, which consists of a recompression supercritical carbon dioxide cycle (RSCO2) and an ammonia-water cooling-power cycle (ACPC). The power system operates in a “self-production and self-sale” mode, which means that the refrigeration capacity produced by the ACPC is utilized to cool the main compressor inlet fluid of the RSCO2. The comprehensive energy and exergy analyses of the proposed novel system are presented. The effects of the six parameters on the system thermodynamic performance are evaluated, which are direct normal irradiation, the ammonia concentration of a basic solution, the pinch point temperature difference of an evaporator, the effectiveness of a recuperator, the pressure ratio of the RSCO2 and the molten salt outlet temperature. The results show that compared with the stand-alone RSCO2, the net power and energy efficiency of the proposed system are improved by 15.94 and 10.61%, respectively. In addition, the increasing ammonia concentration of the basic solution leads to the rise of the ACPC refrigeration output, and the inlet temperature of the main compressor can be declined to 32.97°C with the ammonia concentration of the basic solution of 0.88. Moreover, when the effectiveness of the recuperator in RSCO2 rises up to 0.98, the system energy and exergy efficiencies can reach their maximum value of 30.68 and 33.10%, respectively.